Smart system for real rime optimization of solid waste management in Malaysia - Abu Samah, Mohd Armi; Mohd. Aris, Mohd Shukri; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal; Abdullah Suhaimi, Afiza (2015)

(untitled)
Urbanization is one of the most evident global changes worldwide. The rapid and constant growth of urban population has led to a dramatic increase in urban solid waste production, with a crucial socio-economic and environmental impact. Based on the World Bank Report 2012, 3 billion residents of this earth generate 1.3 billion tons of solid waste per year. Malaysia, with a population of 28 million has produced 33,000 tonnes of solid waste per day in 2012. Thus, this study would developed a new product smart system to ensure the decision making on reduction and well manage solid waste generation are based on knowledge of its task and logical rules or procedures. Development of smart system or expert system will help all users to make real time optimization of solid waste composition generation based on forecasting and also we have good database of solid waste generation particulary. This smart system provided preliminary modules for the design of recycling process to optimize and manage waste composition instead of sending directly to the landfill. It has integrated a Life Cycle Assessment (LCA) that involved with the collection and evaluation of quantitative and qualitative data on the inputs and outputs of material, energy and waste flows associated with a product over its entire life cycle. Waste compositions data from Balakong Selangor were used for validation and verification of the smart system.